Vaginal Lactoferrin Modulates PGE2, MMP-9, MMP-2, and TIMP-1 Amniotic Fluid Concentrations - Alessandro Trentini; Martina Maritati; Carlo Cervellati; Maria C. Manfrinato; Arianna Gonelli; Carlo A. Volta; Fortunato Vesce; Pantaleo Greco; Franco Dallocchio; Tiziana Bellini; Carlo Contini (Mediators of Inflammation)
Inflammation plays an important role in pregnancy, and cytokine and matrix metalloproteases (MMPs) imbalance has been associated with premature rupture of membranes and increased risk of preterm delivery. Previous studies have demonstrated that lactoferrin (LF), an iron-binding protein with anti-inflammatory properties, is able to decrease amniotic fluid (AF) levels of IL-6. Therefore, we aimed to evaluate the effect of vaginal LF administration on amniotic fluid PGE2 level and MMP-TIMP system in women undergoing genetic amniocentesis. One hundred and eleven women were randomly divided into controls (n=57) or treated with LF 4 hours before amniocentesis (n=54). Amniotic fluid PGE2, active MMP-9 and MMP-2, and TIMP-1 and TIMP-2 concentrations were determined by commercially available assays and the values were normalized by AF creatinine concentration. PGE2, active MMP-9, and its inhibitor TIMP-1 were lower in LF-treated group than in controls (p<0.01, p<0.005, and p<0.001, resp.). Conversely, active MMP-2 (p<0.0001) and MMP-2/TIMP-2 molar ratio (p<0.001) were increased, whilst TIMP-2 was unchanged. Our data suggest that LF administration is able to modulate the inflammatory response following amniocentesis, which may counteract cytokine and prostanoid imbalance that leads to abortion. This trial is registered with Clinical Trial number NCT02695563.